The influence of Waterlogging Period on Yield and Yield Components of Mungbean (Vigna radiata L. Wilczek) - Amin, M R; Karim, M A; Khaliq, Q A; Islam, M R; Aktar, S (The Agriculturists, 2018)
Yield performance of 10 selected mungbean (Vigna radiata L. Wilczek) genotypes, viz. GK-7, GK-48, GK-65, VC-6173A, CO-3, IPSA-12, IPSA-13, IPSA-15, BARI Mug-5 and BUmug 2 was evaluated under waterlogged condition in the research field of Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh during April to July 2011. Waterlogging depth was 3-5 cm, created by irrigation from tap water and imposed at 22 days after emergence of seedlings which was maintained for 2, 4 and 6 days in the three different treatments. Yield and yield contributing characters of the mungbean genotypes were significantly affected by waterlogging. The longer the waterlogging period, the more was the reduction in seed yield and yield contributing characters. Among the 10 genotypes, IPSA-13 performed the best in respect of grain yield production under waterlogging condition, which was followed by VC-6173A and BUmung 2. The Agriculturists 2017; 15(2) 88-100